Speech therapy for transgender women (Research, Society and Development, 2021)
Objective: to address aspects related to gender dysphoria and speech therapy, by organizing and providing information about therapeutic principles. Methods: this is a literature review through research in scientific articles in the database Pubmed and Science Direct on the theme of gender dysphoria and voice, in the last 20 years. The research was conduct, by the study authors, from January 2018 to September 2021, with the keywords: (Transgender Persons) OR (Transsexualism) OR (Transsexual) OR (Gender Identity)) AND ((voice training) OR (voice) OR (voice quality)). Results: 31 scientific articles were included in the study. Conclusion: there is a need for multi-professional follow-up and ratifies the importance of speech therapy, since hormonal treatment and laryngeal surgeries do not include all the desired changes in voice and speech in transsexual women. In this way, the speech therapist, besides seeking the elevation of f0, should stimulate the feminine mannerisms, minutiae of the voice and delicacies of the speech. The importance of performing laryngeal surgery combined with speech therapy for voice modification of transgender women was verify.